Identity Formation at Adolescent Stage: Examining the relationship between identity formation and psychological well-being in adolescence (Journal of Advances and Scholarly Researches in Allied Education, 2012)
A successful identity formation is related to beingpsychologically well (Erikson, 1963). This link seems to be lost in theidentity style literature that focuses either  on  the maturity  of  the identity  styles,  or on  adaptive  and maladaptive behaviour correlates ofidentity styles. In this study, we address this lost link. We administered theIdentity Style Inventory (Berzonsky, 1992a) and the scales of PsychologicalWell-Being (Ryff, 1989) to 230 Hellene University students. The Hellenictranslations of the scales functioned appropriately. The findings suggest that,first, avoiding facing identity issues is negatively related to psychologicalwell-being, and, second, when such issues are faced, the way of facing them isnot important.